2009
DOI: 10.1161/atvbaha.108.182584
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Neovascularization by Nanotechnology-Mediated Cell-Selective Delivery of Pitavastatin Into the Vascular Endothelium

Abstract: NP-mediated cell-selective statin delivery may be a more effective and integrative strategy for therapeutic neovascularization in patients with severe organ ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 27 publications
0
65
0
Order By: Relevance
“…Furthermore, the controlled intramyocardial delivery of platelet-derived growth factor was found to improve postinfarction ventricular function with increased vascularization (20). Similarly, in a recent study, the intramuscular injection of pivastatin-loaded nanoparticles that enabled sustained release of the drug resulted in enhanced angiogenesis (21). To enable a sustained release formulation of 1K1, we engineered nanoparticles from poly-lactic acid-glycolic acid (PLGA) copolymer, which is biocompatible and biodegradable and is approved by the FDA.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the controlled intramyocardial delivery of platelet-derived growth factor was found to improve postinfarction ventricular function with increased vascularization (20). Similarly, in a recent study, the intramuscular injection of pivastatin-loaded nanoparticles that enabled sustained release of the drug resulted in enhanced angiogenesis (21). To enable a sustained release formulation of 1K1, we engineered nanoparticles from poly-lactic acid-glycolic acid (PLGA) copolymer, which is biocompatible and biodegradable and is approved by the FDA.…”
Section: Resultsmentioning
confidence: 99%
“…We and others previously showed that (1) the PLGA NP was taken up by cultured SMC mainly via endocytosis, and retained stably in the intracellular space 18,19,21,26,28) . It is likely that after cellular or tissue uptake of NP, NP slowly releases the encapsulated drug (imatinib in this case) into the cytoplasm or Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVEC) were obtained, cultured, and used between passages 4 to 8 21) . Recombinant human VEGF165 (10 ng/mL; R&D) or PDGF at 10 ng/mL was added to the basal medium, and cells (7500 cells per well) were incubated in the presence or absence of imatinib, imatinib-NP, or vehicle for 4 days in 48-well culture plates.…”
Section: Endothelial Cell Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, intimal hyperplasia and subsequent obstruction of the graft causes life-threatening situations and a loss in the quality of life. Macrophage activation and smooth muscle emia 39,49,50) . This therapeutic angiogenesis may be a potential novel therapy for patients with peripheral arterial diseases because there are no available medical therapies other than surgical revascularization.…”
Section: Plga Nanoparticles For the Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%